Seizure increases electroencephalographic abnormalities in children with tuberculous meningitis - Gunawan, Prastiya Indra; Saharso, Darto (Universa Medicina, 2015)
BackgroundTuberculous meningitis (TBM) is a severe intracranial infection with fatal outcomes, permanent disabilities, and electroencephalographic (EEG) abnormalities. Seizures may occur in TBM. The EEG findings in TBM vary according to the site of the inflammatory process. There are few studies describing the EEG patterns and clinical manifestations of TBM. The objective of this study was to investigate the correlation between clinical findings and EEG patterns in children with TBM. MethodsA study of cross-sectional design using medical records was conducted on 12 children with TBM, with their EEG patterns classified as abnormal and normal. Clinical manifestations such as seizures, altered consciousness, headache or fever were collected. A positive cerebrospinal fluids Mycobacterium tuberculosis culture was considered to indicate definitive TBM. Abnormal EEG descriptions were classified into abnormal I, II or III. Correlation between EEG pattern and clinical manifestation were analyzed with Fisher’s exact test. ResultsThe study found cases of 12 children with TBM, the majority presenting with seizures, decreased consciousness and fever. Abnormal EEGs were found in 75% of children and 77% of them showed epileptogenic activities. The EEG results mostly described epileptogenic potentials in the frontotemporal region. There was a significant correlation between EEG abnormality and seizures in children with TBM (p<0.05).ConclusionsThe EEG pattern in children with TBM varies, and EEG abnormalities were more frequently localized in the frontotemporal region. Seizures were associated with EEG abnormalities in children with TBM. EEG abnormalities occurring simultaneously with seizures may predict the occurrence of seizures.